Effect of Grafting Position on Grafting Success Rate of Local Durian (Durio zibethinus L.) from Maluku - Marthini Kristina Lesilolo; Asri Subkhan Mahulette; Sofieka Sania (Agrologia, 2023)
Indonesia is the centre of origin and distribution of durian plants globally, so it has a high genetic diversity of durian plants. Durian propagation can be done vegetatively through grafting. The success of durian grafting is primarily determined by many factors, one of which is the grafting position. This study aimed to examine the best grafting positions on the success rate of grafting of local durian (Durio zibethinus L.) from Maluku. The research was carried out in a nursery located in Telaga Kodok hamlet, Hitulama Village, Leihitu District, Central Maluku Regency, which lasted for six months, namely from December 2021-February 2022. The study was in an experimental form using a randomized block design (RAK) 1 factor with five repetitions. The factor being tested is the position of the grafting, which consists of 5 levels: grafting on the stem hump, grafting 10 cm, 15 cm, 20 cm, and 25 cm above ground level. The study's results obtained information that the grafting position treatment had a significant effect on the percentage of success and the increase in the number of leaves at the end of the observation. The highest rate of grafting success in the study was found in the treatment of the grafting position on the stem stump, which resulted in a success percentage of 98%.